Evaluation of the Effectiveness of Proprioceptive Training According to Radiological Stages in Patients with Knee Osteoarthritis - Sibel Gayretli Atan; Esra Pehlivan; Sinan Bağçacı (Medicina)
Background and Objectives: The aim of the study was to compare the effectiveness of proprioceptive studies according to radiological stages in patients with knee osteoarthritis and to determine at which stage of the disease it should be added to the rehabilitation program. Materials and Methods: This study is a prospective clinical trial. The study was registered with ClinicalTrials.gov (name of the registry: Evaluation of the Effectiveness of Proprioceptive Training According to Radiological Stages in Patients with Knee Osteoarthritis; trial registration number: NCT06150170; date of registration: 21 November 2023). The patients were divided into two groups, which were Grade 1–2 (Group 1) and Grade 3–4 (Group 2) knee osteoarthritis. Both groups underwent a strengthening plus proprioception exercise 3 times a week for 4 weeks. Our primary scale was the Western Ontario and McMaster Universities Arthritis (WOMAC) scale. The secondary outcome measures were pain intensity level, proprioception, range of motion, muscle strength, physical performance, physical activity, quality of life and patient satisfaction. All evaluations were performed twice, before treatment and after 4 weeks of treatment. Conclusions: After treatment, there were significant improvements in pain, range of motion, proprioception, muscle strength, functionality, physical performance and quality of life in both groups (p < 0.05). There was no significant difference between the total WOMAC scores among groups after treatment (p = 0.086). There was more improvement in hip external rotation range of motion in Group 1 (p = 0.022). No significant difference was found in other secondary outcomes (p > 0.05). As a result of this study, we found that proprioceptive training was effective on pain, joint position sense, range of motion, muscle strength, functionality, physical performance and quality of life in patients with knee osteoarthritis in all radiological stages. However, there was no difference between the groups, except for hip external rotation angles.